Barriers and Solutions to the Implementation of Energy Efficiency. A Survey about Stakeholders’ Diversity, Motivations and Engagement in Naples (Italy) - Vassillo, Chiara; Restaino, Daniela; Santagata, Remo; Viglia, Silvio; Vehmas, Jarmo; Ulgiati, Sergio (Journal of Environmental Accounting and Management, 2026)
This paper presents the results of a survey designed to explore the wide range of issues and concerns related to energy efficiency implementation. The survey also assessed the level of engagement of the different kinds of stakeholders and related actors. The International EnergyAgency estimates that energy efficiencymay generate a reduction in global energy demand by 2030, assuming that nations keep recent commitments to energy efficiency policies and that energy efficiency is placed on an equal footing with any other energy resource and it can contribute to the three main challenges of world energy policy: energy security, sustainability and economic development. This reduction will be possible thanks to new technology and stricter government policies, but while overall per capita energy demand is expected to decrease, demand for electricity is foreseen to double by 2060, requiring greater infrastructure investment in smart systems that promote energy efficiency. Energy efficiency advocates also argue that efficiency mprovements can provide social benefits such as increased productivity and employment. Anyway, the actual impact of the energy efficiency implementation remains uncertain. In this framework, engaging all the stakeholders and empowering them as the main actors of these policies and plans becomes crucial. Nevertheless, according to the surveyed stakeholders, uncertainty and concerns about EE policies remain high and call for increased focus on education and good practices.